Hypoxic Brain Injury: An Updated Review for Healthcare Providers - Alshehri, Mohammed Ali Mohammed; Almutiri, Yosif Abdulaziz; Al Raki, Manal Abdullah; Almutairi, Sultan Hamoud Awwadh; Alasmr, Ali Mansour Ali; Alshahrani, Fahd Abdullah; Malakah, -Noha Ashari; Mohammadali, Tahani Abdulrahman; Fadil, Ameera Ahmed; Alrasheedi, Majed Obed Allah; Alrashedi, Manal Suwaylim; Alsharari, Saleh Sabih Saad; et al. (Journal of Ecohumanism, 2024)
Background: Hypoxic brain injury, resulting from inadequate oxygen supply to the brain, is a critical condition that can lead to irreversible neurological damage. The brain’s high metabolic demand and limited energy reserves make it particularly vulnerable to hypoxia and hypoperfusion, which can arise from various causes such as cardiac arrest, respiratory failure, or traumatic injuries. Understanding the pathophysiology, clinical manifestations, and management strategies is essential for optimizing patient outcomes. Aim: This review aims to provide healthcare providers with an updated understanding of hypoxic brain injury, including its etiology, pathophysiology, diagnostic approaches, and evidence-based management strategies, to improve patient care and outcomes. Methods: The review synthesizes current literature on hypoxic brain injury, focusing on its causes, mechanisms, and treatment options. It examines clinical studies, meta-analyses, and guidelines related to therapeutic hypothermia, neuroprotective strategies, and prognostic tools such as imaging, electrophysiological studies, and biomarkers. Results: Hypoxic brain injury leads to a cascade of cellular events, including energy depletion, excitotoxicity, and oxidative stress, culminating in neuronal death. Early intervention, particularly therapeutic hypothermia, has shown promise in improving neurological outcomes. Prognostic tools like MRI, EEG, and serum biomarkers (e.g., neuron-specific enolase) aid in predicting recovery. However, outcomes remain variable, with many patients experiencing severe disability or death despite aggressive treatment. Conclusion: Hypoxic brain injury is a devastating condition requiring prompt and multidisciplinary management. Advances in therapeutic hypothermia, neuroimaging, and biomarkers have improved prognostic accuracy and treatment efficacy. However, further research is needed to refine interventions and enhance long-term outcomes for patients